Are immune checkpoint inhibitors a valid option for papillary renal cell carcinoma? A multicentre retrospective study. (September 2020) - de Vries-Brilland, Manon; Gross-Goupil, Marine; Seegers, Valérie; Boughalem, Elouen; Beuselinck, Benoit; Thibault, Constance; Chevreau, Christine; Ladoire, Sylvain; Barthélémy, Philippe; Negrier, Sylvie; Borchiellini, Delphine; Huillard, Olivier; et al.
Abstract: Background: Papillary renal cell carcinoma (pRCC) is the most common non-clear cell RCC (nccRCC). Pivotal studies evaluating immune checkpoint inhibitors mostly excluded nccRCC. The aim of this retrospective and multicentre study was to evaluate the activity of programmed death-1 (PD-1)/ programmed death-ligand 1 (PD-L1) inhibitors specifically in metastatic pRCC. Methods: The primary end-point was time to treatment failure (TTF). Secondary endpoints included objective response rate (ORR), overall survival (OS) and treatment-related adverse events (TRAEs). Results: From 02/2016 to 01/2019, 57 patients with pRCC were included. Histology included 16 (28%) type 1 pRCC, 34 (60%) type 2 pRCC and 7 (12%) unclassified pRCC. Treatment with immune checkpoint inhibitors was used in the first-line setting in 4 patients (7%), in the second-line setting in 32 patients (56%) and in the third-line setting or more in 21 patients (37%). With a median follow-up of 12 months (95% confidence interval [CI]: 9.9–21.0), the median TTF was 3.1 months (95% CI: 2.7–5.0). Among the 55 patients evaluable for ORR, best response was complete response/partial response in 6 patients (11%), stable disease in 18 patients (33%) and progressive disease in 31 patients (56%). The median OS was 14.6 months (95% CI: 9.0- not reached). TRAEs of grade III–IV were noted in 6 patients (10%) leading to treatment discontinuation, and no grade V TRAEs were observed. Conclusion: PD-1/PD-L1 inhibitors exhibit limited activity as monotherapy in this pRCC population, which remains an unmet need. Our findings underline the need for further prospective clinical trials evaluating immune checkpoint inhibitor combinations in patients with pRCC. Highlights: Papillary renal cell carcinoma (pRCC) is the most common non-clear RCC. We evaluated the efficacy of immune checkpoint inhibitors in metastatic pRCC. Single agent PD-1 inhibitors exhibit limited activity in pretreated metastatic pRCC. Prospective combinations clinical trials are needed in pRCC.